Dosing Cariprazine Within and Beyond Clinical Trials: Recommendations for the Treatment of Schizophrenia - Rancans, Elmars; Dombi, Zsófia Borbála; Barabássy, Ágota (Frontiers in Psychiatry, 2022)
Although the optimal dosing of an antipsychotic medication is known to be essential in the long-term management of schizophrenia, in case of novel drugs such as cariprazine, determining the right dosing strategy is not that simple. Without decades of experience with a particular compound, evidence regarding dosing and titration comes primarily from double-blind, placebo controlled clinical trials that are not necessarily mirroring the real-life experiences of doctors. Via summarizing data from both clinical data (n=3275) and real-world evidence (observational study n=116, case studies n=29), this perspective paper aims to shed a light on the appropriate dosing strategies of cariprazine from treatment initiation through switching strategies to concomitant medications.